Evolutionary Dynamics of Glycoside Hydrolase Family 1 Provide Insights into Insect–Plant Interactions in Lepidoptera - Yanping Yuan; Xidan Zhang; Jinyu Wu; Jun Li; Zhengbo He; Wenbo Fu; Amrita Chakraborty; Shulin He (Insects)
Glycoside hydrolase family 1 (GH1) enzymes are essential for plant cell wall digestion and the detoxification of plant metabolites in insects, yet their evolutionary history in Lepidoptera remains unresolved. This study systematically identified GH1 genes across 61 Lepidopteran genomes and analyzed their evolutionary dynamics. In addition, the expression profiles of GH1 genes in the silkworm (Bombyx mori) across various developmental stages and tissues were related to their evolutionary histories. A total of 996 GH1 genes were annotated and classified into 11 groups, with each showing distinct species diversity. Gene duplication and loss analysis revealed frequent duplications and losses during Lepidoptera evolution; these duplications primarily originated through tandem and dispersed duplications and were located in syntenic regions. Transcriptomic analysis of the silkworm revealed that the groups and duplications of GH1 genes were correlated to their expression patterns, with high expression in the larval midgut and fat body. These findings suggest that GH1 gene duplications and losses and expression have played a significant role in Lepidopteran adaptation to diverse host plants. Overall, this study provides comprehensive insights into the evolutionary trajectories of GH1 genes, highlighting their potential contribution to insect–plant interactions in Lepidoptera.